2014
DOI: 10.1002/mrm.25417
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and exchange dynamics of hyperpolarized 129Xe in human blood

Abstract: The relaxation and exchange analysis performed in this study should provide a sound experimental basis upon which to design future MR experiments for dissolved xenon transport from the lungs to distal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…In the bloodstream, dissolved HP 129 Xe is transported to distal organs by the systemic blood circulation. The longitudinal relaxation time T1 of HP 129 Xe in the human blood is sufficiently long (6 s to 8 s for arterial‐oxygenated blood and 3 s to 4 s for venous‐deoxygenated blood) for it to be detected in the distal organs 10, 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic separation complicates the operational procedures for clinical and preclinical hp 129 Xe MRI. For a number of applications a repeat noble gas delivery at high polarization and concentration levels is needed (6,(30)(31)(32)(33)(34)(35). Additionally, a very constant level of spin polarization is required for molecular imaging with hp 129 Xe biosensors using the hyperpolarized xenon chemical exchange saturation transfer (HyperCEST) methodology (17,(36)(37)(38).…”
mentioning
confidence: 99%
“…The kidney is one of the most well perfused organs in the body, receiving about 20% of the cardiac output through the descending aorta. With a T 1 in blood of approximately 8 seconds and a lung–kidney circulatory transit time of a few seconds, the dissolved 129 Xe can reach the kidneys sufficiently polarized for in vivo MR detection, as demonstrated previously in preliminary work at 1.5 T with MRI and dynamic spectroscopy…”
Section: Introductionmentioning
confidence: 52%